2012
DOI: 10.1097/ede.0b013e31826c2b9e
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Household Transmission Rates of Pertussis and the Effect of Cocooning Vaccination Strategies on Infant Pertussis

Abstract: Selective vaccination of persons in households with a young infant may substantially reduce the disease burden of pertussis in infants by reducing transmission within the household.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 25 publications
6
40
0
8
Order By: Relevance
“…20 The most common source of pertussis infection in infants is typically a household contact. Most often this was mothers followed by fathers and other family members or caregivers, [21][22][23] however, recent studies indicate that other siblings now surpass parents as the infecting source. 24 This change in source of infant infection is likely a combination of increased circulation of pertussis in older children who received their last dose of acellular pertussis vaccine 3 to 5 y previously and in whom immunity has waned, with possible contributions from other control strategies specifically targeted to prevent infant infection.…”
Section: Control Strategiesmentioning
confidence: 99%
“…20 The most common source of pertussis infection in infants is typically a household contact. Most often this was mothers followed by fathers and other family members or caregivers, [21][22][23] however, recent studies indicate that other siblings now surpass parents as the infecting source. 24 This change in source of infant infection is likely a combination of increased circulation of pertussis in older children who received their last dose of acellular pertussis vaccine 3 to 5 y previously and in whom immunity has waned, with possible contributions from other control strategies specifically targeted to prevent infant infection.…”
Section: Control Strategiesmentioning
confidence: 99%
“…5 Implementation of the cocooning strategy has proved difficult in the United States and other countries, with low uptake related to problems in both delivery and funding of the vaccine dose. 6 Although transmission models predicted that cocooning should result in a .50% reduction in the incidence of severe pertussis in young infants, [7][8][9] data on effectiveness in the field has been limited to a hospital-based study from Texas, which found no apparent reduction in infant pertussis hospitalizations despite good uptake of the vaccine among target mothers. 10 In the context of a pertussis epidemic, the government of the Australian state of New South Wales (NSW) undertook in March 2009 to provide Tdap (Boostrix, GlaxoSmithKline, Belgium) free of charge for mothers, fathers, grandparents, and other close adult contacts of infants aged ,12 months.…”
mentioning
confidence: 99%
“…30 Literatürde, bir yaşından küçük bebekler için boğmaca etkeninin ana kaynağının bebeğe yakın aile üyeleri (>%55) olduğu belirtilmektedir. 18,20,21,29,[31][32][33][34][35][36] Ülkemizde yapılan bir çalışmada, bir yaş altı çocuklara boğmacanın %42,8 oranında anneden bulaştığı saptanmıştır. 36 Skoff ve ark.nın ça-lışmasında, boğmaca hastalığına yakalanan bir yaş altı çocuklarda rezervuarın %35,5 oranında kardeş-lerden, %20,6 oranında annelerden ve %10 oranında babalardan olduğu belirlenmiştir.…”
Section: Koza Strateji̇si̇ (Cocooning Strategy)unclassified